1999
DOI: 10.1074/jbc.274.14.9378
|View full text |Cite
|
Sign up to set email alerts
|

HSP27 Multimerization Mediated by Phosphorylation-sensitive Intermolecular Interactions at the Amino Terminus

Abstract: . Using the yeast two-hybrid system, two domains were identified that were responsible for HSP27 intermolecular interactions. One domain was insensitive to phosphorylation and corresponded to the C-terminal ␣-crystallin domain. The other domain was sensitive to serine 90 phosphorylation and was located in the N-terminal region of the protein. Fusion of this N-terminal domain to firefly luciferase conferred luciferase with the capacity to form multimers that dissociated into monomers upon phosphorylation. A del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
311
1
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(338 citation statements)
references
References 64 publications
20
311
1
6
Order By: Relevance
“…The largest molecules with a molecular mass of 600 ± 800 kDa could correspond to about 24 HSP27 subunits (Rogalla et al, 1999). It has been reported that the structure of HSP27 was highly dynamic with small oligomers being in equilibrium with bigger ones (Rogalla et al, 1999;Lambert et al, 1999). This equilibrium can be shifted toward smaller oligomers as a consequence of HSP27 serine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The largest molecules with a molecular mass of 600 ± 800 kDa could correspond to about 24 HSP27 subunits (Rogalla et al, 1999). It has been reported that the structure of HSP27 was highly dynamic with small oligomers being in equilibrium with bigger ones (Rogalla et al, 1999;Lambert et al, 1999). This equilibrium can be shifted toward smaller oligomers as a consequence of HSP27 serine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Human HSP27 contains three sites of phosphorylation at serine residues. The serine 82 corresponds to rodent serine 90 whose phosphorylation was shown to be essential in the reduction of HSP27 complexes to small oligomers (Lambert et al, 1999). This serine is located in a highly variable region that connects the Cterminal a-crystallin domain of the molecule to its Nterminal domains (De Jong et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorylation reduces the average oligomer size, and increases oligomeric polydispersity and rate of subunit exchange of αBc [98,[132][133][134], whereas it leads to a dramatic decrease in the size of Hsp27 oligomers, such that the triply phosphorylated isoform is predominately dimeric in solution [135,136]. Thus, under stress conditions, Hsp27 is phosphorylated, triggering dissociation of the high molecular mass Hsp27 oligomers [117,135,137,138] and an increase in the amount of exposed hydrophobicity on the newly formed Hsp27 dimers [139]. Phosphorylation also affects the cellular distribution of some sHsps.…”
Section: Phosphorylationmentioning
confidence: 99%